Dobry żart Nobla wart! O edukacyjnych walorach niektórych odmian dowcipu słownego - Krzyżewska, Jolanta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In the functioning of contemporary school, humour may stimulate many positive social phenomena – friendly interactions, creating a playful climate for task activities, problem solving in groups, etc. This allows for the implementation of „joyful education”, in the sense of creating the most favourable developmental conditions for the child to acquire knowledge. As the definition itself indicates, such education has creative qualities and is typical of the initial educational stages – pre- and early school education. Verbal humour, as a category of humour distinguished due to its exceptional heuristic value, seems to reveal another possibility – of treating it as a specific instrumentarium for solving or even spotting and formulating problems. It is this role of verbal humour which provides space for its applications in further stages of school education.
Keywords: creative education; direct method; indirect method; humor; linguistic joke; verbal humor